Remedy Efficiency through Paclitaxel on Rat (Rattus norvegicus) Brain Injury and Risk Premium of N- Diethyl nitrosamine (DEN) Injection - Bashdar Saeed Hamad amin; Bushra Ahmed Hamdi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
AbstractThe current study deals with the effect of N-Diethylnitrosamine (DEN) induced traumatic brain injury on male albino rats, as well as the outcome results of treatment with paclitaxel nanoparticles for a period of 8 weeks with two-week intervals is the concern of the present study. Mean body weight, as well as brain weight, was considered as the main parameters whereas a detailed immunohistochemical study on rat brain sections was performed. Astrocytic biomarkers for the diagnosis of astrocytes by fibrillary glial acidic protein (GFAP). Neuronal GFAP staining used for various broke sections were forwarded. Comparison and Contrast of all these parameters in all steps of the experiment had been discussed. The efficiency of the treatment was found to be evident. The effect on body weight was significant whereas brain weight results showed insignificant differences. A longer duration of treatment may well reflect more significant results.